Metamaterial based compact antenna design for UWB applications - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
In this paper, a compact Ultrawideband (UWB) high gain microstrip patch antenna using planar metamaterial structures is proposed. The antenna has two layers of metamaterial structure which are made by etching π-shaped slot on main radiating patch and crossed shaped slots on the ground plane. The inductances and capacitances developed due to the ground plane and patterned radiating patch leads to the left handed behavior of the metamaterial. The proposed antenna has compact size 27.6×30.8mm2 with height 1.6mm and designed on low cost FR4 substrate. The impedance bandwidth (-10dB) of the antenna is 3-12GHz with average gain of 4dBi and the peak gain 5.8 dBi at 9.5 GHz. The results obtained from the simulation studies shows that the antenna has good radiation characteristics for the UWB applications. ©2014 IEEE.